Pemberdayaan Masyarakat Kawasan Karst Melalui Pengelolaan Air dan Strategi Ketahan Pangan di Biraeng - Salma Samputri; Badrizal Al Hazar; Fitri Handayani; Nurul Aulia Bohari; Muhammad Zulfi Al'Ghani; Atsari Rafi (Jurnal Pemberdayaan Masyarakat, 2026)
This community service activity aims to address the critical challenges of clean water availability and food security faced by communities in the karst area of Biraeng Village, Pangkep Regency, which is characterized by fragile geological conditions and rapid drainage. These conditions result in limited surface water availability and have a negative impact on agricultural productivity. Data was collected through field observations, in-depth interviews, and documentation to obtain a comprehensive understanding of the social and environmental conditions. The results show that the community relies on dug wells, seasonal springs, rainwater harvesting, and bore wells, whose discharge decreases during the dry season, thereby requiring a collective water distribution management system. Community empowerment through the establishment of water management groups has proven effective in improving more equitable and organized access to water. In addition, food diversification programs, such as cultivating corn, cassava, and utilizing home gardens, have been effective in maintaining local food availability despite environmental limitations. However, challenges such as limited technical knowledge and underdeveloped local institutions remain significant constraints. Therefore, this study recommends strengthening local institutions in a sustainable manner, integrating appropriate technology, and developing food diversification strategies based on local potential to achieve food security and sustainable water resource management in karst areas.